The Impact of COVID-19 on Socio Economic Condition of City People: Lessons From the Selected KCC Area - Haque, Md Nazmul; Ansar, Saifullah Bin; Biswas, Gitisree; Islam, Md Razzakul; Mamun, Abdullah Al (Journal of Engineering Science, 2020)
This paper aims to provide a small-scale quantitative overview about the impact on socio economic condition in lockdown wards of Khulna City Corporation (KCC), Bangladesh due to this pandemic. Online survey for primary data was conducted through 158 respondents and the informants belongs to different types of occupation such as student, govt. employee, businessman etc. Secondary data was obtained from various credential sources. With the socioeconomic stress of COVID-19, people’s satisfaction level is measured with well-known index life scale assessment to measure the judgmental component of subjective well-being. This study reveals that 44% respondents who preferred online based activities which are directly related with online activity and occupation related activities rather than physically involved activities (33%) due to maintain social distancing. Besides about 46% maid was suspended due to hygienic concern and 45% driver was suspended because of the inability of maintenance cost i.e. an economic pressure which has been reflected on all classes of people. According to life scale assessment, 35% people were slightly dissatisfied and only 1% of them are extremely satisfied during this situation. It means that maximum of the people allows their living condition to be in the less satisfied range during this pandemic situation. Besides, hospital accessibility has been analyzed among the lockdown wards and it is observed that ward no.-24 whose has good accessibility with 292 m distance from the locality but poor condition has been observed in ward no.-17. To attenuate these ill socioeconomic conditions, initiatives of inclusive cooperation of different stakeholders should be taken spontaneously. Journal of Engineering Science 11(2), 2020, 117-126